Efficient oxygen reduction reaction using mesoporous Ni-doped Co3O4 nanowire array electrocatalysts1. Issue 36 (28th September 2015) - Tong, Xili; Xia, Xinhui; Guo, Congxiu; Zhang, Yongqi; Tu, Jiangping; Fan, Hong Jin; Guo, Xiang-Yun
<x xml:space="preserve">Abstract</x> Mesoporous Ni-doped Co3O4 nanowire arrays synthesized via a simple hydrothermal process exhibit high electrochemical activity and a four-electron transfer characteristic, with superior tolerance to methanol and CO, and better stability compared to a commercial Pt/C catalyst.